Real-time acid production and extracellular matrix formation in mature biofilms of three Streptococcus mutans strains with special reference to xylitol - Ikäläinen, Henna; Guzman, Camilo; Saari, Markku; Söderling, Eva; Loimaranta, Vuokko (Elsevier B.V., 2025)
Background
Acidogenicity and production of an extracellular matrix (ECM) are important virulence factors for the dental caries-associated bacteria, such as Streptococcus mutans, that live in biofilms on tooth surface. The ECM protects the bacteria from the flushing and buffering effects of saliva resulting in highly acidic microenvironments inside the biofilm.
Materials and methods
In this in vitro study, we applied real-time assays to follow biofilm formation and pH decrease in a growth medium and saliva by three S. mutans strains, as well as acid neutralization inside the mature biofilm. Results were compared with the biofilm composition. Effects of a non-fermentable polyol, xylitol, on acid production and acid neutralization in mature biofilms were evaluated by real-time pH measurements and confocal microscopy.
Results
Combination of real-time pH measurements with biofilm accumulation assays revealed growth media dependent differences in the pH decrease and biofilm accumulation, as well as strain differences in acid production and biofilm formation but not in the buffer diffusion through ECM. The presence of xylitol reduced the pH drop during biofilm formation of all strains. In addition, with strain Ingbritt xylitol reduced the amount of ECM in biofilm, which increased the rate of acid neutralization inside the biofilm after buffer exposure.
Conclusion
Our results stress the importance of biofilm matrix in creating the acidic environment inside a S. mutans biofilm, especially in the presence of saliva. In addition, our results suggest a novel mechanism of xylitol action. The observed increase in the permeability of the S. mutans ECM after xylitol exposure may allow acid-neutralizing saliva to reach deeper layer of the biofilms and thus, in part, explain previous clinical observations of reduced plaque acidogenicity after frequent xylitol use.